Effect of pad roughness on shear strength of thin small leadless package - Ong, Cheng Guan (2018)
Thin Small Leadless Packages (TSLP) have been manufactured to cater the current industry demand for a smaller electronic apparatus with a higher electrical performance. Previous studies showed the solder joint strength of leadless package with the printed circuit board (PCB) using Ni-P/Sn-0.5 Ag solder were influenced by soldering and reflow parameters. Nevertheless, scattered studies have been reported on the effect of surface roughness (Ra) of leadless package on its solder joint strength. The current study investigated effect of Ra of TSLP on the solder joint strength between the TSLP and PCB. In the current study, Ra of package’s contact pad were varied using different Cu alloy leadframe materials (i.e. C194 and EFTECH-64) and etching process parameters (i.e. pH, specific Cu density and conveyor speed). This study also investigated the effect of Ni-P plating thickness and solder reflow conditions (i.e. temperature and duration) on the solder joint strength. Shear test was conducted on the soldered samples using Dage Series 4000 Bond Tester as per Infineon’s Control Plan Specifications, with the shear strength data represented the solder strength values. Subsequently, the discussion of solder strength results were supported by the failure mode results of the shear test samples, generated by scanning electron microscopy (SEM, JOEL JSM-6360A) images and energy dispersive X-ray (EDX, JOEL JSM-6360A) analysis. An increase of Ni-P thickness on the etched samples reduced their Ra, thus resulted in a higher solder joint strength and smaller strength variation. Porous solder region in the soldered samples contributed to Mode 1 failure (i.e. fracture at solder region), which were exhibited by more than 80% of shear test samples. Only small percentages of shear samples showed Mode 2 (i.e. fracture at IMC and Ni-P layer interface) and Mode 3 (i.e. fracture at Ni-P and Ni bump interface). The percentage of Mode 2 and 3 failures were lower (i.e. composed of less than 5% of shear test samples) in low Ra samples. This could be explained by the improved solder wettability and strengthening of the IMC layer on the low Ra Ni-P plated samples.